A nanosecond pulsed laser-ablated MWCNT-Au heterostructure: an innovative ultra-sensitive electrochemical sensing prototype for the identification of glutathione. Issue 17 (27th July 2022) - Kaimal, Reshma; Senthilkumar, Periyathambi; Aljafari, Belqasem; Anandan, Sambandam
Abstract : Here, a scheme that aptly describes the reduction of gold nanoparticles' crystalline size on the surface of MWCNTs in an aqueous phase to generate a LAMWCNT-Au heterostructure, employing an Nd:YAG laser (energy = 505 mJ and λ = 1064 nm) is developed. Abstract : Here, a scheme that aptly describes the reduction of gold nanoparticles' crystalline size on the surface of MWCNTs in an aqueous phase to generate a LAMWCNT-Au heterostructure, employing an Nd:YAG laser (energy = 505 mJ and λ = 1064 nm) is developed. Such a LAMWCNT-Au heterostructure results in the development of an easy electrochemical procedure based on voltammetry analysis for ultra-sensitive glutathione sensing. High-resolution transmission electron microscopy, UV-visible spectroscopy, Raman spectroscopy, and X-ray photoelectron spectroscopy were used to examine the composition and morphology of laser-ablated adhesion of AuNPs over the MWCNT heterostructure. With a wide dynamic range of 0.1–9 μmol L −1, the LAMWCNT-Au heterostructure can detect glutathione with a high sensitivity of 0.1186 μA (μmol L −1 ) −1 at the low limit of detection (LLOD; 0.93 μmol L −1 ). It improves electron transfer and promotes redox reactions by increasing the conductivity and surface area. The findings show that the fabricated LAMWCNT-Au/GCE is an effortless and potent biosensing prototype for the identification of glutathione (GSH) at a negative potential in a neutral medium. The substantial synergistic surface impact produced by the introduction of AuNPs over MWCNTs exhibits exceptional electrocatalytic activity in comparison with individual MWCNT and AuNP. Moreover, the LAMWCNT-Au heterostructure has excellent selectivity, long-term stability, and reproducibility, and it can easily separate target molecules that were identified using various voltammetric analyses.